DESIGNING A GO-TO-MARKET STRATEGY IN ENTERING THE ELECTRIC VEHICLE REPAIR MARKET IN INDONESIA TO INCREASE NEW CUSTOMER ACQUISITION - Erry Akbar Pratama; Sonny Rustiadi (LPPM STIE Muhammadiah Bandung, 2025)
This study aims to develop a go-to-market strategy for PT. APMS in entering the electric vehicle body repair service market in Indonesia. This study uses a qualitative method with primary data collection through semi-structured interviews with key stakeholders such as company management, suppliers and customers, as well as secondary data such as academic literature and industry reports. External analysis is carried out using the PESTEL and Porter's five forces frameworks, then internal analysis is carried out using the Value chain and VRIO frameworks. The (STP) segmentation, targeting and positioning approach, value proposition canvas and 7Ps' marketing mix are used to design an effective go-to-market strategy. The results of the study indicate that the electric vehicle market in Indonesia is expected to continue to grow, thus becoming an opportunity for PT. APMS to develop, PT. APMS has competitive advantages such as a strong reputation and network of relationships. The proposed go-to-market strategy includes selecting the right market, understanding customer needs, developing appropriate products, selecting effective channels and an integrated multi-channel marketing system.